2023
DOI: 10.3389/fnut.2023.1286633
|View full text |Cite
|
Sign up to set email alerts
|

Soft and energy drinks consumption and associated factors in Saudi adults: a national cross-sectional study

Abeer M. Aljaadi,
Abrar Turki,
Arwa Z. Gazzaz
et al.

Abstract: IntroductionThe consumption of soft and energy drinks poses a significant risk for non-communicable diseases, such as diabetes and heart disease. Studies in Saudi Arabia have reported elevated consumption of soft/energy drinks, but nation-wide data is not available. Therefore, this study aims to explore the prevalence of soft and energy drinks consumption and its associated factors among a representative sample of Saudi adults.MethodsThe present research is a secondary data analysis of the 2021 Sharik Diet and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Nevertheless, these studies reported high consumption of soft drinks by the Saudi and UAE populations. Aljaadi, Turki, Gazzaz, et al (2023) found that -About 67% reported consuming soft drinks at least once a week, with more males than females reporting weekly consumption.‖ Exhibit 1 shows the UAE and Saudi Arabia's high consumption of soft drinks with a rate of 103 and 89 liters per person per year, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these studies reported high consumption of soft drinks by the Saudi and UAE populations. Aljaadi, Turki, Gazzaz, et al (2023) found that -About 67% reported consuming soft drinks at least once a week, with more males than females reporting weekly consumption.‖ Exhibit 1 shows the UAE and Saudi Arabia's high consumption of soft drinks with a rate of 103 and 89 liters per person per year, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There is continuous development in this industry, with producers regularly introducing new products to the market that differ in composition, flavour, as well as unique colouring or labels designed to attract specific consumers. Currently, producers are offering increasingly innovative solutions, such as caffeine shots, 'sugar-free' drinks, or beverages enriched with natural ingredients, aligning with the current trend of promoting a healthy lifestyle [4]. Due to intense competition in the energy drink market, manufacturers place significant emphasis on marketing, often utilizing viral marketing strategies.…”
Section: Introduction and Objectivementioning
confidence: 99%